The Scottish Enlightenment Human Nature, Social Theory and Moral Philosophy: Essays in Honour of Christopher J. Berry. - Mills, R. J. W. (Edinburgh University Press, 2021)
11 specially commissioned essays examine the Scottish Enlightenment's contributions to commercial society, the 'science of human nature' and the emergence of the modern political economy.